DIGITAL INNOVATION IN HALAL LOGISTICS: AN INDONESIAN CASE STUDY - Nurhayati, Nurhayati (Agripreneur : Jurnal Pertanian Agribisnis, 2023)
This study explores the changing importance of digital technology in the field of Halal logistics in Indonesia. The study focuses on the integration and effects of Internet of Things (IoT), Artificial Intelligence (AI), and blockchain technologies. These advancements are crucial for increasing operational effectiveness, guaranteeing adherence to strict Halal regulations, and promoting visibility and traceability in the supply chain. Indonesia's unique strategy in embracing these technologies is emphasised in the report, establishing a standard in the global Halal industry. Furthermore, it tackles the obstacles encountered by the industry, including constraints in infrastructure, financial repercussions, and the deficiency in skills required to effectively utilise these digital tools. The report conducts a comparative examination of worldwide practices, highlighting Indonesia's distinctive role in spearheading digital innovation in Halal logistics. Moreover, it provides concrete suggestions for professionals in the field and delineates prospective areas of investigation, highlighting the possibilities of developing technologies and the necessity for longitudinal studies to assess the enduring effects of these digital incorporations. This extensive investigation provides essential perspectives on the impact of digital transformation on certain logistics sectors, such as Halal logistics, within the diversified and dynamic market of Indonesia.